IMPLIKASI YURIDIS PERUBAHAN ANGGARAN DASAR PERSEROAN TERBATAS YANG DILAKUKAN OLEH NOTARIS TANPA ADA KEPUTUSAN RAPAT UMUM PEMEGANG SAHAM (RUPS) - Nur Andayani (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2016)
Abstract Amendements to the Articles of Association of the Company Limited set out in article 19 to article 27 of Law No. 40 of 2007 on Limited Liability Companies, where the provisions of the articles mentioned that amendments to the Articles of Association must be made through the General Meeting of Shareholders, hereinafter the Meeting must listed on the agenda of the amendment in question. The purpose of the study the researchers did was to describe and analyze about the legality of the amendment to the Articles of Association due to the negligence committed by Notary change the Articles of Association of the Company Limited without the client's request and to know the efforts - efforts to be made by the parties to restore the tenure of the board the company Limited under the Articles of Association of the original. To answer these problems the research method used is empirical juridical doing sociological juridical approach and a case study approach. Research based on the case with the Limited Liability Companies PT. BPR